The competency and awareness level of anti-money laundering & counter financing terrorism (AML/CFT) risk judgment amongst malaysian banking compliance officers/ Muhammad Nasrul Asyraf Azli and Rosmawati Haron - Azli, Muhammad Nasrul Asyraf; Haron, Rosmawati (UiTM Cawangan Johor, 2024)
Literature studies unveiled a new issue about money laundering risk judgment, focusing on impaired decision-making to detect suspicious activities and the quality of suspicious transaction report (STR) submission to the Central Bank of Malaysia. To address this issue, the research aims to seek and to provide empirical evidence quantitatively on the different levels of competency and awareness amongst Malaysian banking compliance officers, factors that could significantly reflect their anti-money laundering and counter-financing of terrorism (AML/CFT) risk judgment outcome. The research also seeks to examine using the demographic profiles as the controlled variable to determine further the differences if demographic profiles could really play an important role in shaping AML/CFT risk judgment outcome. A series of questionnaires were distributed amongst Malaysian banking compliance officers using purposive and snowball sampling. 34 responses were returned within a month and were adequate to identify the suggested differences using non-parametric studies. The analyses of this research resulted in Malaysian banking compliance officers' competency and awareness levels being high and satisfactory. However, there were disparities amongst them derived from various demographic profiles, such as educational background which may lead to inconsistency of requirements in the compliance regulation. The limitation of this paper is that it only focuses on Malaysian banking compliance officers in view of their competency and awareness level. Future research should consider covering in much broader scope to address AML/CFT risk judgment issues and other factors that may cause poor AML/CFT risk judgment, such as the organisation’s compliance program and corporate governance, training method, internal and external regulations which may lead to an impaired STR submission to the Central Bank of Malaysia.